A study on Summary of Discharge Diagnosis on Neurosurgery at Thammasat University Hospital - Wongfung, Kamonwan (Thammasat University Hospital Journal Online, 2022)
Background: Neurosurgery requires a lot of resources to treat. From the current practice for diagnostic codes, summary of principal diagnosis, comorbidity, complication, surgery and procedure are often incomplete. This problem affects the hospital fee reimbursement of Thammasat University Hospital. Objective: 1) To study the results of the summary of the diagnosis of surgical and surgical diseases that affects hospital fee reimbursement. 2) To study the quality of medical records regarding discrepancies affecting Adjust Relative Weight (AdjRW.). 3) To compare the differences in hospital fee reimbursement before and after the discrepancies of discharge diagnosis. Material and methods: The sample group was inpatient neurosurgery medical records in all treatment benefit schemes and discharged from January 2021 to June 2021. The total 491 charts were assessed by using the criteria for assessing the summary of diagnosis and procedures of the physicians summary assessment (SA)version-2018 and to study the results of conclusions of the diagnosis. Data were analyzed by frequency distribution, percentage and comparison of sample data with Wilcoxon Signed Rank Test statistic. Result: From a total of 491 samples, There were 144 inpatient medical records that were inaccurate Inaccuracies in the conclusion of the diagnosis, 144 procedures and surgeries, accounting for 29.33 percent. After revision, this practice had added a 120 (24.4%) discrepancies that affects AdjRW.were found 510.5541 AdjRw. which increased the compensation for medical services by 53.03 percent of the amount difference after the discrepancy was detected. Conclusion: It is important to accurately, complete the medical rewards the including discase and procedure, that affect AdjRW. This will allow hospitals to receive more reimbursement for their medical services based on the actual expenses.